MIMO Positioning for IMT-Advanced Systems Based on Geometry Approach in NLOS Environments - Awang Md Isa, Azmi (Penerbit Universiti, UTeM, 2011)
In wireless communications, one of the main problems that deteriorate the accuracy of location and positioning (L&P) estimation is non line of sight (NLOS) propagation. With the advances of multiple input multiple output (MIMO) technology as one of the features of International Mobile Telecommunications-Advanced (IMT-Advanced) systems, it has become feasible to adopt the technology into the mobile location scenario. By exploiting the multipath characteristics of the MIMO system, it is possible to estimate the position of mobile stations (MS) by considering the capability of MIMO to mitigate the effects of non line of sight (NLOS) conditions. In this paper we developed geometric approach by utilizing the advantages of MIMO system and employ the time of arrival (TOA) as range measurements for improving location estimation in various NLOS environments. The performance of the proposed method has been evaluated through computer simulation. The results of our simulation demonstrate the advantages of the proposed algorithm in comparison with the conventional LLS algorithm meeting the Federal Communications Commission (FCC) requirements.